Cecal Microbiota of Free-Range Hens Varied With Different Rearing Enrichments and Ranging Patterns - Bari, Md Saiful; Kheravii, Sarbast K.; Bajagai, Yadav S.; Wu, Shu-Biao; Keerqin, Chake; Campbell, Dana L. M. (Frontiers in Microbiology, 2022)
Free-range pullets are reared indoors but the adult hens can go outside which is a mismatch that may reduce adaptation in the laying environment. Rearing enrichments might enhance pullet development and adaptations to subsequent free-range housing with impact on behavior and health measures including gut microbiota. Adult free-range hens vary in range use which may also be associated with microbiota composition. A total of 1700 Hy-Line Brown® chicks were reared indoors across 16 weeks with three enrichment treatment groups: ‘control’ with standard litter housing, ‘novelty’ with weekly changed novel objects, and ‘structural’ with custom-designed perching structures in the pens. At 15 weeks, 45 pullet cecal contents were sampled before moving 1386 pullets to the free-range housing system. At 25 weeks, range access commenced, and movements were tracked via radio-frequency identification technology. At 65 weeks, 91 hens were selected based on range use patterns (‘indoor’: no ranging; ‘high outdoor’: daily ranging) across all rearing enrichment groups and cecal contents were collected for microbiota analysis via 16S rRNA amplicon sequencing at V3-V4 regions. The most common bacteria in pullets were unclassified Barnesiellaceae, Prevotella, Blautia and Clostridium and in hens unclassified, Ruminococcus, unclassified Lachnospiraceae, unclassified Bacteroidales, Paraprevotellaceae YRC22, and Blautia. The microbial alpha diversity was not significant within the enrichment/ranging groups (pullets, P ≥ 0.17, hen rearing enrichments groups, P ≥ 0.06, hen ranging groups, P ≥ 0.54), but beta diversity significantly varied between these groups (pullets, P ≤ 0.002, hen rearing enrichments groups, P ≤ 0.001, hen ranging groups, P ≤ 0.008). Among the short-chain fatty acids (SCFA), the propionic acid content was higher (P = 0.03) in the novelty group of pullets than the control group. There were no other significant differences in the SCFA contents between the rearing enrichment groups (all P ≥ 0.10), and the ranging groups (all P ≥ 0.17). Most of the genera identified were more abundant in the indoor than high outdoor hens. Overall, rearing enrichments affected the cecal microbiota diversity of both pullets and adult hens and was able to distinguish hens that remained inside compared with hens that ranging daily for several hours.